Sry and the hesitant beginnings of male development - Polanco, Juan Carlos; Koopman, Peter (Developmental biology, 2007)
In mammals, Sry (sex-determining region Y gene) is the master regulator of male sex determination. The discovery of Sry in 1990 was expected to provide the key to unravelling the network of gene regulation underlying testis development. Intriguingly, no target gene of SRY protein has yet been discovered, and the mechanisms by which it mediates its developmental functions are still elusive. What is clear is that instead of the robust gene one might expect as the pillar of male sexual development, Sry function hangs by a thin thread, a situation that has profound biological, medical and evolutionary implications.